Synthesis, X-ray crystal structure, Hirshfeld surface analysis, and molecular docking studies of DMSO/H2O solvate of 5-chlorospiro[indoline-3,7'-pyrano[3,2-c:5,6-c']dichromene]-2,6',8'-trione - Sharma, Varun; Banerjee, Bubun; Sharma, Aditi; Gupta, Vivek Kumar (European Journal of Chemistry, 2021)
The title compound, 5-chlorospiro[indoline-3,7'-pyrano[3,2-c:5,6-c']dichromene]-2,6',8'-trione was synthesized via one-pot pseudo three-component reaction between one equivalent of 5-chloroisatin and two equivalents of 4-hydroxycoumarin using mandelic acid as catalyst in aqueous ethanol at 110 °C. The synthesized compound was characterized by FT-IR, 1H NMR, and HRMS techniques. Single crystals were grown for crystal structure determination by using single X-ray crystallography technique. It was found that the crystals are triclinic with space group P-1 and Z = 1. The crystal structure was solved by direct method and refined by full-matrix least-squares procedures to a final R-value of 0.0688 for 6738 observed reflections. The crystal structure was stabilized by elaborate system of O-H···O, N-H···O, and C-H···O interactions with the formation of supramolecular structures. 3D Hirshfeld surfaces and allied 2D fingerprint plots were analyzed for molecular interactions. Molecular docking studies have been performed to get insights into the inhibition property of this molecule for Human topoisomerase IIα.